Design Thinking in Action: How Pre-Service Biology Teachers Represent Abstract Concepts Through Learning Media - Kintan Limiansi; Ema Aprilisa; Anggi Tias Pratama; Kintan Limiansih (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2026)
Background: The development of biology learning media requires pedagogical skills, conceptual understanding, and representation skills. However, research examining how pre-service teachers integrate these three elements in the design thinking process to develop learning media is still very limited. This study aims to identify the types of biological concepts chosen by pre-service biology teachers in the development of learning media, investigate how they represent abstract biological concepts, and analyze their thinking process in designing learning media. Methodology: The study employed a concurrent mixed-methods design to examine pre-service biology teachers’ design thinking through analysis of blueprints and photos of learning media developed by seven groups; data were coded for concept types, representation types, and design thinking processes, with only concept types analyzed quantitatively using percentage calculations across groups. Findings: The results showed that the types of biological concepts selected were structure, system, and process. The consistency of all groups in using visual representations, symbols, and narratives for all types of concepts demonstrates the pedagogical awareness of pre-service biology teachers regarding the importance of integrating multiple representations to support meaningful concept understanding. From a design thinking perspective, students went through the stages of empathy, defining problems, generating ideas, and selecting the media to be developed. Contributions: This study shows that pre-service biology teachers have developed representational competence, but they still tend to prioritize visual appeal over conceptual support. These findings recommend strengthening pre-service biology teachers’ skills in designing learning media that promote deep conceptual understanding, not merely visual appeal